Uma coluna ausente : Lefort leitor de Merleau-Ponty. filosofia existencial e o pensamento do político - Bruno Victor Parreiras Soares Melo (2022)
This thesis intends to reconstruct the work of the French philosopher Claude Lefort based on a clear interpretative bet: in order to be correctly understood, his work must be read from the thought and unthought of his teacher and friend Maurice Merleau-Ponty. The chiasm between the visible and the invisible, the sense and the non-sense, is what we understand to express the absent column represented by Merleau-Ponty. The death of a friend expresses an undeniable absence, at the same time that it is capable, in the philosophical sphere, of producing signs and meanings in our own expression of thought. It is from this consideration that we will seek to defend the existence of a work of Merleau-Ponty's oeuvre, with an importance similar to that which Lefort dedicates to Machiavelli in his grandiloquent thesis. Placing the two projects in a more explicit dialogue than the objectively considered essays do, is therefore our main hypothesis, given that a work of thought, when successful, exceeds its present field, launching itself into intense transcendence for future readers and to a world to which he does not have the key. We will see how fundamental concepts for the work of Merleau-Ponty are resignified and reworked by Lefort within the scope of political philosophy, or rather, his impetus to think about the political being twists the concepts in order to make them speak what was only an intention or a noble repression. The notion of institution, thus, illuminates the democratic revolution and the modus operandi of this regime that lives in the test of its own “institution”. The wild spirit descends from the Merleau-Pontyan ontology to think about savage democracy, the contesting spirit that flees from all theoretical pretensions, coming to the public world to question the established power, making room for us to think about the indomitable power of democracy. These are all expressions of the “discovery of the political”, which takes place in recognition of the insufficiency of Marxism in thinking about the complexity of democratic and totalitarian regimes. This criticism is announced in Merleau-Ponty in the 1950s in his abandonment of the philosophy of the history of the proletariat, without, however, carrying the necessary radicalization to found a political philosophy in place of the great edifice that represents Marxism. This is Lefort's philosophical project, therefore, which will be built through the dialectic that institutes the void to understand democracy, interpretation and expression where meaning walks.